PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA HUNTU SELATAN KECAMATAN BOLANGO SELATAN KABUPATEN BONE BOLANGO - Abdurrahman Idji, Rusly; Yadi Wardana, I Wayan (STISIPOL Mujahidin Buol, 2023)
is research aims to obtain an overview of how community participation in development in South Huntu Village, South Bolango District, Bone Bolango Regency, uses a qualitative research method using a descriptive approach. Data collection techniques are carried out through interviews, observation and documentation. The research results show that: Participation. decision making is carried out by involving the community who are active in providing suggestions and bright ideas for the progress of the village, community involvement in the Implementation of Programs or Projects is carried out through deliberations at the Hamlet level which are followed by Village deliberations which are attended by community leaders, religious leaders, RT / RW, sub-district government along with BPD or LPM in the context of exploring ideas. From exploring these ideas, the problems that exist in the village can be identified. Community participation in the implementation of benefits is carried out through community participation, voluntary involvement, giving of oneself directly in helping with all things related to development to support the implementation of development in the form of money, energy, goods, materials, thoughts or information that are useful for implementing development, while participation in decision making is carried out by involving the community who are active in providing suggestions and bright ideas for the progress of the village.